Anti-inflammatory and Protective Properties of Daphnetin in Endotoxin-Induced Lung Injury - Yu, Wen-wen; Lu, Zhe; Zhang, Hang; Kang, Yan-hua; Mao, Yun; Wang, Huan-huan; Ge, Wei-hong; Shi, Li-yun (Journal of agricultural and food chemistry, 2014)
Uncontrolled inflammatory responses cause tissue injury and severe immunopathology. Pharmacological interference of intracellular pro-inflammatory signaling may confer a therapeutic benefit under these conditions. Daphnetin, a natural coumarin derivative, has been used to treat inflammatory diseases including bronchitis. However, the protective effect of daphnetin in inflammatory airway disorders has yet to be determined, and the molecular basis for its anti-inflammatory properties is unknown. This paper shows that daphnetin treatment conferred substantial protection from endotoxin-induced acute lung injury (ALI), in parallel with reductions in the production of inflammatory mediators, symptoms of airway response, and infiltration of inflammatory cells. Further studies indicate that activation of macrophage and human alveolar epithelial cells in response to lipopolysaccharide (LPS) was remarkably suppressed by daphnetin, which was related to the down-regulation of NF-κB-dependent signaling events. Importantly, this study demonstrates that TNF-α-induced protein 3 (TNFAIP3), also known as A20, was significantly induced by daphnetin, which appeared to be largely responsible for the down-regulation of NF-κB activity through modulation of nondegradative TRAF6 ubiquitination. Accordingly, the deletion of TNFAIP3 in primary macrophages reversed daphnetin-elicited inhibition of immune response, and the beneficial effect of daphnetin in the pathogenesis of ALI was, partially at least, abrogated by TNFAIP3 knockdown. These findings demonstrate the anti-inflammatory and protective functions of daphnetin in endotoxin-induced lung inflammation and injury and also reveal the key mechanism underlying its action in vitro as well as in vivo.